Analysis of clinical profile, growth and developmental pattern of twin babies in a tertiary care hospital of central India - Ghanghoriya, Pawan K.; Agrawal, Avyact; Mohan, Uthara; K., Keerthi; Singh, Shivraj (International Journal of Contemporary Pediatrics, 2018)
Background: Twin birth is associated with increased risk of neonatal morbidity and mortality and disadvantages in growth and neurodevelopmental status than singletons. Objective of present study was to analyze the clinical profile, growth pattern and neurodevelopmental outcome of twin babies on follow up for 6 months corrected gestational age. Methods: A prospective observational study was done in a tertiary care NICU in 81 pairs of twins (162 neonates). Initial assessment in terms of morbidities and mortality was followed by growth pattern and neurodevelopmental assesment using DDSTII of survived infants upto 6 months corrected gestational age. Results: Prematurity was present in 75% of twin gestation. 95.1% were LBW, 4.9% were normal birthweight. 38.9% were AGA babies and 61.1% were SGA babies. Moderate to severe growth discordancy, was identified in 17.2% of the twins. Mortality was inversely proportional to birth weight and gestational maturity and directly proportional to birth weight discordance. Most of the complications were attributed to prematurity and low birth weight. RDS, hypoglycemia (16%), Perinatal asphyxia (19%), NEC, shock, hyperbilirubinemia were major complications. Feeding difficulties need special attention. Group I (28-32 weeks) lagged behind group I (32-37 weeks) and group III (>37weeks) in all anthropometric parameters like weight, height and head circumference at all the ages. Growth velocity was in the order group I (28-32 weeks) >group II (32-37) >group III (>37). At 6 months of there was high incidence of abnormal neurodevelopmental outcome among twins according to gestational age. Hypoglycemia, Perinatal asphyxia, RDS, and NEC were risk factors of NDD. Conclusions: There is higher incidence adverse outcomes in terms of morbidity, mortality, growth and development among twins.